Severe hypoglycemia induced by Tigecycline in a diabetic and hemodialysis patient - Puca, Entela; Puca, Edmond; Vrekaj, Klei; Puca, Dea (The Journal of Infection in Developing Countries, 2024)
Introduction: Tigecycline has a broad spectrum of activity, including activity against drug-resistant Gram-positive and -negative microorganisms. Its side effects are significant, but hypoglycemia is a rare finding during treatment. We aim to present an event of severe hypoglycemia in a patient with type 2 diabetes mellitus with replacement renal therapy, and hemodialysis after initiating tigecycline. Case presentation: A 54-year-old female diagnosed with type 2 diabetes mellitus was under treatment with basal-bolus insulin therapy and oral antihypertensive drugs. She started hemodialysis 24 months ago. She complained of recurrent fever for the last seven months and was treated with several antibiotics. In two separate blood cultures, she tested positive for methicillin-resistant Staphylococcus epidermidis (MRSE). Based on the antibiogram, we started treatment with tigecycline 100 mg/day. After 6-8 hours from the first dose, the patient is complicated with events of hypoglycemia and then continues with severe hypoglycemia (40-47 mg/dL). The patient continued to have hypoglycemia for about 16-18 hours after the last dose. We didn’t find any reasons to explain the cause of episodes of hypoglycemia. She did not have high blood insulin levels (insulin 4.11 mIU/L [range 2.6-24.9]). We followed her for six months and the patient did not experience episodes of hypoglycemia. Conclusions: The association of severe hypoglycemia with tigecycline treatment is a very rare event and published papers on this topic are limited. Clinicians should be aware of this rare event when administering tigecycline and should routinely check blood glucose level during the treatment.